THE ANALYSIS OF DARK TRIAD CONCEPT IN THE SONG LYRICS OF METALLICA’S “MASTER OF PUPPETS” AND “SAD BUT TRUE” - Kristiawan, Yohanes Angie; Adhitya, Galant Nanta; Enjelin, Eka Meysel (Rubikon : Journal of Transnational American Studies, 2024)
The dark triad personality is commonly understood in the field of psychological studies. However, the analysis of the dark triad is still relatively new in the realm of literary studies. This article presents the dark triad in the lyrics of Metallica’s songs “Master of Puppets” and “Sad but True”. The selection of these two songs is based on the popularity of the song and the choice of words that cause multiple interpretations among Metallica fans. The findings of this research show that there are three traits of the dark triad found in both song lyrics. Machiavellianism represents manipulation; narcissism represents self-admiration; psychopathy represents anti-social and cruelty. This article can hopefully provide in-depth understanding to listeners as the music from previous decades keeps making comebacks.